The Influence of Country of Origin Image, Brand Image, and Product Quality on Purchase Decisions for Some By Mi Products (A Case Study of Consumers in Jakarta) - Sofiarridha Nur Ayuni; Ibnu Haris; Sulfarid Sulfarid (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of country of origin image, brand image, and product quality partially and simultaneously on purchasing decisions. The type of research used is quantitative. The population in this study are consumers of Some By Mi products in the city of Jakarta whose number is unknown. The process of data collection and population in this study by distributing questionnaires via the Google Forms link. The sample taken was 96 respondents using the Cochran formula in determining the number of samples. The data collection method used a questionnaire and the analysis technique used was multiple linear regression. The results of the analysis show that: 1) The country of origin image variable has a positive and significant effect on purchasing decisions. 2) The brand image variable has a negative and significant effect on purchasing decisions. 3) The product quality variable has a positive and significant effect on purchasing decisions.